2020
DOI: 10.3390/diagnostics10010030
|View full text |Cite
|
Sign up to set email alerts
|

The Genes—Candidates for Prognostic Markers of Metastasis by Expression Level in Clear Cell Renal Cell Cancer

Abstract: The molecular prognostic markers of metastasis are important for personalized approaches to clear cell renal cell carcinoma (ccRCC) treatment but markers for practical use are still missing. To address this gap we studied the expression of ten genes—CA9, NDUFA4L2, VWF, IGFBP3, BHLHE41, EGLN3, SAA1, CSF1R, C1QA, and FN1—through RT-PCR, in 56 ccRCC patients without metastases and with metastases. All of these, excluding CSF1R, showed differential and increased (besides SAA1) expression in non-metastasis tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
(65 reference statements)
0
13
0
8
Order By: Relevance
“…NDUFA4L2, which is one of the important components of the ETC complex I subunit in mitochondria, is an important site for ROS generation and is widely involved in the regulation of biological processes. Previous research showed the expression of NDUFA4L2 was increased in multiple cancer cells, including clear cell renal cell cancer, 16,30 hepatocellular carcinoma 14 and colorectal cancer 17 . NDUFA4L2 knockdown has a profound antiproliferative effect in HIF1α‐positive cell lines 18 .…”
Section: Discussionmentioning
confidence: 99%
“…NDUFA4L2, which is one of the important components of the ETC complex I subunit in mitochondria, is an important site for ROS generation and is widely involved in the regulation of biological processes. Previous research showed the expression of NDUFA4L2 was increased in multiple cancer cells, including clear cell renal cell cancer, 16,30 hepatocellular carcinoma 14 and colorectal cancer 17 . NDUFA4L2 knockdown has a profound antiproliferative effect in HIF1α‐positive cell lines 18 .…”
Section: Discussionmentioning
confidence: 99%
“…CORO2B was found to be involved in many biological processes of malignant transformation in BEAS-2B cells induced by cigarette smoke (Wang et al, 2019 ). LOC51089, also called C1QA, was found to be involved in the innate immune system and was associated with the expression of PD-L1 (Olkhov-Mitsel et al, 2020 ), and its abnormal expression in tumor tissues was confirmed in head and neck squamous cell carcinoma and clear cell renal cell carcinoma (Yu et al, 2019 ; Apanovich et al, 2020 ). MXRA8 is one of the predicted tumor stroma-specific markers in various cancers (Kiflemariam et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-induced NDUFA4L2 attenuates mitochondrial oxygen consumption by inhibiting complex I activity, which limits intracellular ROS production under low oxygen conditions (30). The significance of NDUFA4L2 expression in the development of ccRCC was first demonstrated by research from our group (31) and Fu et al (32) and was subsequently followed by the works of other researchers (12,(33)(34)(35). NDUFA4L2 expression is also increased in non-small cell lung cancer (NSCLC) cell lines cultured under hypoxic conditions.…”
Section: Genementioning
confidence: 97%